Effect of the matrix on the 1.5 microm photoluminescence of Er-doped silicon quantum dots - Cerqueira, M. F. (2006)
Erbium doped nanocrystalline silicon thin films were produced by reactive magnetron r.f. sputtering. Their structural and chemical properties were studied by micro-Raman, spectroscopic ellipsometry and Rutherford backscattering spectroscopy. Films with different crystalline fraction and crystallite size were deposited by changing the deposition parameters. The impact of the composition and structure of Erbium ions environment on the 1.5 microm photoluminescence is discussed.